(untitled) (Bangladesh Heart Journal, 2017)
A total of 58 patients of severe mitral stenosis with Wilkins score < 10 were studied, all of them underwent PTMC. Spirometry and peak expiratory flow rate were done before and after PTMC. A follow up echocardiographic assessment of successful PTMC and pulmonary artery systolic pressure were taken. Two patients died of PTMC related procedural complications. There was no dropout. Hemodynamic measurements obtained by echocardiography showed improvement of mean mitral valve area from 0.764 ± 0.1257 cm2 to 1.404 ± 0.1194 cm2 after PTMC (p < 0.001). Transmitral peak pressure gradient decreased from 26.43 + 5.62 mmHg to 11.36 + 2.40 mmHg after PTMC (p < 0.001). Pulmonary artery systolic pressure was decreased from 57.73 ± 17.03 mmHg to 31.27± 8.30 mmHg after the procedure (p < 0.001). pulmonary functions - The mean FEV1 was increased from 60.18 ± 13.054 to 78.32 ± 11.874 after PTMC (p<0.001). The mean FVC was 53.80+ 12.313 before PTMC, which significantly improved to 68.57 + 11.662. PEF also showed an improvement from 223.75 + 62.3215 to 372.05 + 62.2. (p<0.001). Bangladesh Heart Journal 2017; 32(1) : 45-49